Turkish migration to Europe: A modified gravity model analysis - Dinçer Dedeoğlu; H. Deniz Genç (IZA Journal of Development and Migration, 2017)
This study specifies and applies a gravity model to provide empirical evidence on determinants of emigration from Turkey to 31 destination European countries over the period between 1960 and 2013. Results under alternative estimation strategies show that economic, demographic and cultural factors have significant influence on migration decision to the destination countries. The model has explanatory power and is useful for testing the given hypothesized determinants of migration from Turkey to 31 European countries from perspective of the country of origin.
Keywords: F22; F14; C33; 330; Migration; Gravity model; Panel data; Turkey